Pulmonary embolism risk in hospitalized patients with nonalcoholic fatty liver disease: A case-control study. Issue 45 (11th November 2022) - Zeina, Abdel-Rauf; Kopelman, Yael; Mari, Amir; Ahmad, Helal Said; Artul, Suheil; Khalaila, Ali Sleman; Taher, Randa; Villannueva, Fernando Zertuche; Safadi, Rabea; Abu Mouch, Saif; Abu Baker, Fadi
Abstract : Abundant research has associated nonalcoholic fatty liver disease (NAFLD) with atherosclerosis, but very few reports have evaluated the association between NAFLD and venous thromboembolism. We aimed to investigate the association between NAFLD and pulmonary embolism (PE) in hospitalized patients. In this retrospective case–control study, we included consecutive patients from 2 university-affiliated hospitals who were referred for CT pulmonary angiograms for a suspected PE. Patients with a history of excessive alcohol consumption, chronic liver diseases or cirrhosis were excluded. The imaging studies of the entire cohort were reviewed by 2 expert radiologists who confirmed the diagnosis of PE and examined the liver to detect and grade hepatic steatosis. Accordingly, patients were categorized into NAFLD patients and non-NAFLD controls. Patient demographics, medical history, hospitalization details as well as patients' outcomes were documented. Multivariate analysis was performed to identify predictors for developing PE and hazard ratios with corresponding 95% confidence intervals were estimated. A total of 377 patients (101 with NAFLD and 276 controls) were included. NAFLD patients had significantly higher BMI values (33.16 ± 6.78 vs 26.81 ± 5.6; P  < .001) and prevalence of diabetes (41 (40%) vs 85 (30.8%); P  = .03). The prevalence of PE was significantly higher in the NAFLD group (80 (79.2%) vs 147 (53.3%), P  < .001). In a multivariate analysis, older age, recent surgery or trauma, active malignancy, smoking, and NAFLD (HR ratio = 4.339, P  < .0001 and 95% CI = 2.196–8.572) were independently associated with PE development. Patients with NAFLD were associated with an increased risk of developing PE independent of other classical risk factors for PE.